Pengaruh Social Media Marketing terhadap Brand Image My Pangandaran Tour and Travel - Silvy Damayanti; Arianis Chan; Cecep Safa'atul Barkah (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
Tour & Travel Agent is an old type of business that can still maintain its potential as a business opportunity every year. This is due to the use of the internet, thus presenting the online travel market. One of the travel agency businesses that use the internet, especially social media, as a marketing medium to build a company brand image is MyPangandaran. However, the growth of followers on the @mypangandarantours Instagram account is relatively slow, and the level of follower engagement is still low. This study aims to find out how MyPangandaran grows a positive brand image for followers of their Instagram account, @mypangandarantours. In addition, to see the influence that social media has had on followers of brand images on their Instagram accounts. The method used in this research is quantitative with the type of associative survey research. The data technique uses analysis from observations, literature studies, interviews and questionnaires. The sample in this study was 96 followers of the @mypangandarantours Instagram account. The sampling technique used non-probability sampling, namely purposive sampling. The data analysis technique used simple linear regression analysis. This study indicates a significant influence of social media on the brand image of followers of the @mypangandarantours Instagram account, meaning that if the social media marketing variable is getting better, the brand image will be getting better.